Utilization of fly ash in construction - Norhaiza, Ghazali; Khairunisa, Muthusamy; Saffuan, Wan Ahmad (IOP Publishing Ltd, 2019)
In year 2016, Malaysia produce about 6.8 million tonnes of fly ash from six coal fired electric power station and this figure will increase due high demand of electric production. Fly ash is a waste product from the combustion of pulverized coal in electricity power plants and considered as a contributing factor for air, water and soil pollution that lead to human health problems and various geo-environmental issue. However, fly ash can be converted into valuable and useful product if properly utilized and many researches has been carried out in aim to increase the utilization of fly ash in various sectors especially in construction sector. In line with current economic conditions, all construction works required cost efficient with good quality of work. Therefore, fly ash is suitable to be used as an alternative raw material to enhance or replacing the existing construction material. In produce construction material many different industries and construction because it is oxide-rich material. The paper will be discussing the potential of managing waste of fly ash by utilizing it as construction materials.